2021
DOI: 10.2196/26456
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of an Analytic Tool for Predicting the Fall Risk in Inpatients: Controlled Interrupted Time Series

Abstract: Background Patient falls are a common cause of harm in acute-care hospitals worldwide. They are a difficult, complex, and common problem requiring a great deal of nurses’ time, attention, and effort in practice. The recent rapid expansion of health care predictive analytic applications and the growing availability of electronic health record (EHR) data have resulted in the development of machine learning models that predict adverse events. However, the clinical impact of these models in terms of pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…The fall-prevention CDS intervention was more significantly associated with decreasing injurious falls for patients aged 65 and older. Following previous studies, 4 , 13 the present trial demonstrated that integrating machine-learning predictions and guideline-driven CDS functions into the EMR could help to reduce the considerable physical and cognitive burdens experienced by nurses when they are ensuring patient safety. To improve the effectiveness of this intervention further, combining already-known effective strategies might help to decrease fall rates, such as routine patient and family engagement and other quality improvement tools.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The fall-prevention CDS intervention was more significantly associated with decreasing injurious falls for patients aged 65 and older. Following previous studies, 4 , 13 the present trial demonstrated that integrating machine-learning predictions and guideline-driven CDS functions into the EMR could help to reduce the considerable physical and cognitive burdens experienced by nurses when they are ensuring patient safety. To improve the effectiveness of this intervention further, combining already-known effective strategies might help to decrease fall rates, such as routine patient and family engagement and other quality improvement tools.…”
Section: Discussionsupporting
confidence: 56%
“…This was the first fall-prevention clinical study to provide evidence for combining a machine-learning technique and CDS functions for EMR systems. A previous evaluation 13 of the feasibility of fall-risk prediction using machine learning found that changes in nurse behavior resulted in significant improvements in risk-targeted, preventive activities. In the current study, we added more-sophisticated CDS functions to the EMR system to remind nurses about guideline-driven activities tailored to patient-level risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supervised learning trains algorithms based on labeled training data, whereas the unsupervised learning approach does not require labeled training and can find structures within the data. Several EHR-based MLAs have been developed for fall risk predictions in hospitalized patients [ 14 - 18 ]. Few studies have explored the utility of ML approaches for senior residents in community-dwelling or long-term assisted living facilities [ 19 - 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly,Cho et al (2021) was the only study where nurses in clinical practice used an AI-based system across six hospital units for real-world clinical validation. The AI-based fall prediction tool was trialled alongside a standardized falls risk assessment to determine which was more accurate in identifying older patients at risk of falling and to encourage nurses to implement falls prevention strategies, with the intervention group implementing more falls risk targeted interventions.…”
mentioning
confidence: 99%